2020
DOI: 10.1016/j.fuel.2019.116810
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of methane/hydrogen/air premixed flame in a closed channel with inhibition

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For example, the local flame extinction, combustion stability and power output of CH 4 combustion were found to be improved with H 2 enrichment [16,17]. Moreover, it has been demonstrated that the thermal and chemical effects of H 2 addition increased significantly the flame dynamics and combustion efficiency of premixed CH 4 flames [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…For example, the local flame extinction, combustion stability and power output of CH 4 combustion were found to be improved with H 2 enrichment [16,17]. Moreover, it has been demonstrated that the thermal and chemical effects of H 2 addition increased significantly the flame dynamics and combustion efficiency of premixed CH 4 flames [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…In the context of premixed combustion systems, the design of the combustor plays a critical role in determining flame characteristics and overall combustion performance [4][5][6]. Recently, studies have been conducted to investigate the flame behavior and shape changes due to hydrogen mixing due to the combustion rate of hydrogen seven times faster than methane [7][8][9]. The targets to be overcome in hydrogen-methane combustion are the large amount of NOx generated due to high-temperature flames [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its extremely low ignition energy, wide explosive limits, and higher laminar burning velocity, the explosion risk of hydrogen gas is much higher than other hydrocarbon fuels [10,15,16], there are many safety problems in the application of hydrogen energy, such as hydrogen embrittlement [13] and detonation. The intense pressure, high temperature, and strong shockwaves generated during methane and hydrogen gas explosions can cause severe casualties and property damage [17], while their fuel mixtures will inevitably have different ignition and combustion characteristics, posing significant safety hazards in the production, use, storage, and transportation processes of hydrogen-blended fuels [18][19][20][21]. The fuel mixture of hydrogen and methane is known as hythane, which is expected to become an alternative clean energy source.…”
Section: Introductionmentioning
confidence: 99%